Indianapolis : the true story of the worst sea disaster in U.S. naval history and the fifty-year fight to exonerate an innocent man - Vincent, Lynn; Vladic, Sara (Simon & Schuster, 2018)
"Based on years of original research and new reporting, two acclaimed authors deliver the riveting and emotionally wrenching full story of the worst sea disaster in United States naval history: the sinking of the USS Indianapolis during World War II--and the fifty-year fight to exonerate the captain after a wrongful court martial."--Provided by publisher.